2021
DOI: 10.9745/ghsp-d-20-00550
|View full text |Cite
|
Sign up to set email alerts
|

Improving Services for HIV-Exposed Infants in Zambia and Cameroon Using a Quality Improvement Collaborative Approach

Abstract: Although the designs of the QICs varied to fit local contexts in Cameroon and Zambia, they used similar indicators and methods, and each resulted in improvement of testing coverage and timely return of test results for HIV-exposed infants.nThe social dynamics of the QIC approach enhanced the sense of shared purpose and community, fostered teamwork and friendly competition, and built leadership support while creating an internal enabling environment at the facility level. The quarterly learning sessions, monthl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…However, we found quality improvement interventions undertaken in other health areas [ 22 , 25 , 26 ]. One sought to improve waiting time by means of hospital-wide quality improvement, using the Strengthening Laboratory Management Toward Accreditation model [ 22 ]; another sought to improve early infant diagnoses coverage, timely return of HIV test results, and initiation of antiretroviral treatment using the Quality Improvement Collaborative approach [ 25 ]; and another sought to improve the adherence and cure of patients with tuberculosis, by using SMS text message reminders [ 26 ]. We also found 2 studies [ 23 , 24 ] that aimed at investigating patients’ satisfaction with the quality of health services [ 23 ] and the undertaking of antiretroviral treatment [ 24 ].…”
Section: Introductionmentioning
confidence: 98%
“…However, we found quality improvement interventions undertaken in other health areas [ 22 , 25 , 26 ]. One sought to improve waiting time by means of hospital-wide quality improvement, using the Strengthening Laboratory Management Toward Accreditation model [ 22 ]; another sought to improve early infant diagnoses coverage, timely return of HIV test results, and initiation of antiretroviral treatment using the Quality Improvement Collaborative approach [ 25 ]; and another sought to improve the adherence and cure of patients with tuberculosis, by using SMS text message reminders [ 26 ]. We also found 2 studies [ 23 , 24 ] that aimed at investigating patients’ satisfaction with the quality of health services [ 23 ] and the undertaking of antiretroviral treatment [ 24 ].…”
Section: Introductionmentioning
confidence: 98%
“…RESPONSE: This is the first study targeting the improvement of waiting time and satisfaction in ophthalmology in Cameroon. Other quality improvement studies were found [3][4][5], including those that aimed at investigating patients' satisfaction with the quality of health care services [6] and the undertaking of antiretroviral treatment [7]. Our choice of setting has been explained and similar studies are alluded to.…”
Section: Minor Commentsmentioning
confidence: 99%
“…When attributing improvements to the QIC, this project shares several key limitations with most QI initiatives, including multiple other QICs that ICAP has supported in LMIC. [35][36][37][38][39][40] First, the fact that site-level activities and interventions were deliberately flexible, adaptable and changed over time in response to real-time data makes analysis of 'fidelity' unhelpful. Second, the absence of control or comparison sites means that external factors may have confounded our analysis.…”
Section: Lessons and Limitationsmentioning
confidence: 99%